Missionaries, Miners, and Indians Spanish Contact with the Yaqui Nation of Northwestern New Spain, 1533-1820 - Hu-DeHart, Evelyn (University of Arizona Press, 1981)
The Yaqui Indians managed to avoid assimilation during the Spanish colonization of Mexico. Even when mining interests sought to wrest Yaqui labor from the control of the Jesuits who had organized Indian society into an agricultural system, the Yaqui themselves sought primarily to ensure their continuing existence as a people. More than a tale of Yaqui Indian resistance, Missionaries, Miners, and Indians documents the history of the Jesuit missions during a period of encroaching secularization. The Yaqui rebellion of 1740, analyzed here in detail, enabled the Yaqui to work for the mines without repudiating the missions; however, the erosion of the mission system ultimately led to the Jesuits' expulsion from New Spain in 1767, and through their own perseverance, the Yaqui were able to bring their culture intact into the nineteenth century.